2022
DOI: 10.1007/s11517-022-02543-x
|View full text |Cite
|
Sign up to set email alerts
|

A robust and parsimonious machine learning method to predict ICU admission of COVID-19 patients

Abstract: In this article, we discuss the development of prognostic machine learning (ML) models for COVID-19 progression, by focusing on the task of predicting ICU admission within (any of) the next 5 days. On the basis of 6,625 complete blood count (CBC) tests from 1,004 patients, of which 18% were admitted to intensive care unit (ICU), we created four ML models, by adopting a robust development procedure which was designed to minimize risks of bias and over-fitting, according to reference guidelines. The best model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Famiglini et al [ 32 ] devised several machine-learning models predicting ICU admission of COVID-19 patients within the next five days using gender, age and the complete blood count as potential features. Their best model achieves a ROC-AUC of 0.85 and a Brier score of 0.144.…”
Section: Discussionmentioning
confidence: 99%
“…Famiglini et al [ 32 ] devised several machine-learning models predicting ICU admission of COVID-19 patients within the next five days using gender, age and the complete blood count as potential features. Their best model achieves a ROC-AUC of 0.85 and a Brier score of 0.144.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are several studies around the world using machine learning tecnique based on different characteristics easily obtained from patients with COVID-19 [13] , [18] , [40] and different outcomes such as need for intensive care, mechanical ventilation and death, among others. Among these characteristics, laboratory test data have also been used in machine learning prediction models, rather than subjective data that could vary between geographic regions, ethnic characteristics, observers and institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes et al (2021) developed a ML model to predict the risk of ICU admission, use of mechanical ventilation and/or death analysing a database of 1,040 patients from a hospital in Brazil, using the routine biomarkers lymphocytes, CRP and ferritin, together with Intensive Care Unit (ICU) scores [17] . Famiglini et al (2022) developed ML models for the prediction of ICU patient admission using only Complete Blood Count (CBC) data from Italy [18] , which has been further externally tested in databases from multiple countries [19] , but had the worst performance rates in the Brazilian ones. All of these studies aimed to predict the risk of ICU admission, and some of them used parameters other than routine blood biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Gabr et al found significantly more atypical monocytes in ICU patients 26 , while Pezeshki et al did not identify any statistically significant associations between blood findings and clinical course 21 . Importantly, several non-hematologic factors (e.g., age, gender), and other laboratory parameters (including ferritin, C-reactive protein, interleukin-6) are often associated with death, and machine learning-based algorithms have been employed for diagnosis and prediction of care needs and outcome 35 , 36 , 37 .…”
Section: Introductionmentioning
confidence: 99%